DAMPAK PELAKSANAAN PROGRAM PENGEMBANGAN KECAMATAN (PPK) DALAM MENGENTASKAN KEMISKINAN DI KABUPATEN BANYUMAS (STUDI KASUS DI KECAMATAN KEDUNG BANTENG) - Dijan Rahajuni; Endang Sri Gunawati; Suprapto Suprapto (Solusi, 2020)
Study about " The Impact of District Development Programs (Program Pengembangan Kecamatan) To Ease the Poverty in Banyumas Region". The Aim of this research are to determine and analyze the performance of District Development Programs, the influence of District Development Programs toward income per capita, and the influence of District Development Programs to ease and increase prosperity, study case in Kedungbanteng, Banyumas.The Data include primary data that got from 4 groups in each village with the amount 128 people as sample of group member in Kedungbanteng district, and the village consist of Kedungbanteng village, Karangnangka and Melung. The Period of research is on July 2009. The analysis method that use are with the proportion, tabulation, and comparation each variables.The result of this research are:I.The performance of District Development Programs ( PPK = Program Pengembangan Kecamatan) in the term of the influences in Kedungbanteng area in the capital availablelity point of view is significant enought with the average 4 7, 17 percent and the targeting point is 60, 70%.2. The contribution income activity of SPP (woman lending money) from PPK is 48,82 % toward income per capita including significant enought.3. All of responden that got the impact from PPK is above from poverty line, and for the using of business activity in 3,73 times from KFM but for the using of lending money not for business activity is 2,54 times from KFM.4. The level of respondent income that proper in KHL only got the benefit that using lending money activity of business activity from Kedungbanteng area.Therefore it is suggested that the lending of money was so needed and proper to continue, but it must be more selected with direct cross check the availability of business activity each member and needed empower with good quality of member of PPK to determine the business prospect and good management.Keywords: Program Pengembangan Kecamatan, kemiskinan, simpan pinjam perempuan, kebutuhan fisik minimum, kebutuhan hidup layak.